All-atomistic molecular dynamics study of the glass transition of amorphous polymers. (21st July 2022) - Tang, Zhiye; Okazaki, Susumu
Abstract: Glass transition is an intensively studied topic but many questions in this regard remain unaddressed. This is an important phenomenon related to the physical and mechanical properties of amorphous polymer materials. In this study, existing and newly performed all-atomistic molecular dynamics (MD) simulations of polycarbonate (PC) and poly-(methyl methacrylate) (PMMA) cooling processes were analyzed to address their glass transitions from a molecular perspective. Additionally, potential energy, radius of gyration, dihedral transition, and end effects were characterized. Further analyses were performed to characterize the individual degrees of freedom (DoFs) by the variance, correlation between two DoFs by the correlation coefficient, and collective motions by instantaneous normal mode (INM) analysis. Various DoFs experienced glass transition at temperatures slightly different from the glass transition temperature T g, presumably owing to their different spatial scales and chemical environments. This suggests that the experimentally observed broad T g may be attributed to a similar hierarchy of motions. Collective motions characterized by INM revealed slightly different behaviors for PC and PMMA. Graphical abstract: Image 1 Highlights: T g of million-atom atomistic models of PC and PMMA were investigated by MD. Potential energy, Rg, dihedral transition, end effect across T g were characterized. Abrupt variance uprises and peaks in correlation showed local DoFs' responses to T g . Hierarchy of local DoFs' characteristic temperatures possibly widened T g range. INM showed responses to T g at low mode and differences between PC and PMMA.